Biliary phosphatidylcholine and lysophosphatidylcholine profiles in sclerosing cholangitis - Gauss, Annika; Ehehalt, Robert; Lehmann, Wolf-Dieter; Erben, Gerhard; Weiss, Karl Heinz; Schäfer, Yvonne; Klöters-Plachky, Petra; Stiehl, Adolf; Stremmel, Wolfgang; Sauer, Peter; Gotthardt, Daniel (World journal of gastroenterology, 2013)
Biliary phosphatidylcholine and lysophosphatidylcholine profiles in sclerosing cholangitis
Gesehen am 28.01.2020